FACTORS PREDICTING THE INTENTION TO USE SOCIAL NETWORK OF MONKS IN BANGKOK - ศศิธนากรแก้ว ศรัณย์ธร (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2018)
This research “Factors Predicting the Intention to Use Social Network of Monks in Bangkok” is aimed to 1) study the relationship between technology self-efficacy, perceived usefulness, perceived ease of use, subjective norms and intention to use social network and 2) to examine factors that predict intention to use social network. Data are collected by survey questionnaires from 400 respondents. Research results are analyzed with frequency, percentage, mean, standard deviation and multiple regression analysis. The results of the study found that technology self-efficacy, perceived usefulness, perceived ease of use and subjective norms had positively correlated with intention to use social network at significant level 0.05. All of four factors predicted intention to use social network at significant level 0.05 and could explain intention to use social network with a percentage of 44.0